2018
DOI: 10.3390/su10051522
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Labeling and Retailer Pricing Strategies: The U.K. Haddock Market

Abstract: Abstract:In attempts to differentiate their store imagery, grocery retailers frequently introduce new products, which are often rich in extrinsic attributes such as claims regarding healthiness and environmental sustainability. This paper explores retailers' pricing strategies for product attributes of haddock in the United Kingdom. The results show that retailers' pricing strategies vary, in particular for extrinsic product attributes such as eco-labels and country-of-origin. The high price premium generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Furthermore, we found, as expected, a significant and negative impact of sales Promotion on prices (-18.5%). Results agree with those outlined by Bronnmann & Hoffmann (2018) and by Zhang et al (2018).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we found, as expected, a significant and negative impact of sales Promotion on prices (-18.5%). Results agree with those outlined by Bronnmann & Hoffmann (2018) and by Zhang et al (2018).…”
Section: Resultssupporting
confidence: 92%
“…It is well established that consumers perceive home country-of-origin as being of higher quality than foreign ones (Verlegh & Steenkamp, 1999). This is consistent with findings outcome by Loke et al (2015) and Zhang et al (2018). Moreover, Tempesta & Vecchiato (2013), conducting a choice experiment with the aim to investigate the willingness to pay (wtp) a premium price for milk (considering origin, area of production and rearing method) found that people living in the northern of Italy tend to prefer milk produced in north-centre Italy, properly because of the affective and the cognitive components that affect the preferences for home country-of-origin products.…”
Section: Resultssupporting
confidence: 87%
“…Direct observation provides the primary advantage of richer information on product characteristics, particularly for all attributes associated with claims reported on the label. Such product characteristics are usually missing data in a commercial database collected automatically through store scanners [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…HPM has been extensively used to analyze differentiated markets [31,32,33,34,35,36,37]. It has been used by environmental economists [38,39,40], in labor economics [41] and in agricultural economics [25,42,43,44,45]. No previous study has studied implicit prices for attributes of gluten-free food.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, country-of-origin labeling is mandatory in many countries (Asche, Larsen, Smith, Sogn-Grundvåg, & Young, 2015). Studies have found price premiums of 10-25% for ecolabels on products of Alaska pollock, Atlantic cod, haddock, and salmon in the UK (Asche et al, 2015;Roheim, Asche, & Santos, 2011;Sogn-Grundvåg, Larsen, & Young, 2013Zhang, Sogn-Grundvåg, Asche, & Young, 2018). A number of studies show similar premiums or a positive willingness to pay for ecolabeled seafood in other markets, although the results are more mixed with respect to country-of-origin labeling (Asche & Bronnmann, 2017;Br ecard, Hlaimi, Lucas, Perraudeau, & Salladarr e, 2009;Fonner & Sylvia, 2015;Garlock, Nguyen, Anderson, & Musumba, 2020;Uchida, Onozaka, Morita, & Managi, 2014;Wakamatsu, Anderson, Uchida, & Roheim, 2017).…”
Section: Introductionmentioning
confidence: 99%